Relationship Between Nurses' Response Time and Patients' Anxiety Level at The Emergency Room of Murni Teguh Ciledug Hospital in Tangerang - Fitriani, Dini; Tambunan, Dior Manta (Journal of health research and technology, 2026)
Response time is the time needed by patients to get help that is appropriate to the emergency of their illness since entering the Emergency Room. Nurse’s response time is often the cause of a patient experiencing anxiety. The purpose of this study was to determine whether there is a significant relationship between nurses’ response time and patient’ anxiety levels at the Emergency Room (ER) of Murni Teguh Ciledug Hospital in Tangerang. This type of research is quantitative research with a cross-sectional study design. The sampling technique in this study was accidental sampling and the sample size in this study amounted to 100 respondents. Data analysis used the Spearman Rho test. The results of this study with the Spearman Rho test showed a relationship between response time and patient anxiety levels in the ER of Murni Teguh Ciledug Hospital with a p-value = 0.033 (α<0.05). It is recommended to conduct further research with more samples and add variables of environmental conditions, types of diseases and previous experiences.